Tumor volume quantification in emission tomography - Ahmed Abdel Mohymen Mohamed Abdel Naby; Ahmed Soltan Abdel Monem; Said Ali Taha; Hamed Ibrahim Farag; Sameh Mostafa Reda (2025)
This thesis investigates the optimization of quantitative accuracy in emission tomography, with particular emphasis on tumor volume and standardized uptake value (SUV) measurements in PET/CT imaging. Advanced reconstruction techniques, including time of flight (TOF) and point spread function (PSF) modeling, were evaluated to assess their impact on recovery coefficients, image quality, and quantitative reliability. The influence of reconstruction parameters such as matrix size, voxel size, number of iterations and subsets, and postfiltering was systematically analyzed. The results demonstrated that optimized reconstruction settings significantly improve tumor volume quantification while reducing partial volume effects and Gibbs artifacts. Furthermore, adherence to international harmonization guidelines enhances reproducibility and comparability across different PET systems. These findings support the use of tailored reconstruction strategies to achieve accurate and reliable quantitative PET imaging for clinical and research applications
(3JgOa gPg GdOQGSI Edi JMSjf ObI GdbjGSGJ GdcejI aj GdJUhjQ GdebWYj HGdEUOGQ GdHhRjJQhfj(B/(3GdCTYI GdebWYjI (B(PET/CT)(3, eY GdJQcjR Ydi JMOjO MLe GdhQe hbjeI GdGeJUGU GdbjGSjI (B(SUV). (3Je Jbjje JbfjGJ EYGOI GdHfGA GdeJbOeI, HeG aj Pdc Ref GdWjQGf (B(TOF) (3hOGdI GdGfJTGQ GdfbWjI (B(PSF)(3, dOQGSI JCKjQgG Ydi eYGedGJ GdGSJQOGO hLhOI GdUhQI hObI GdbjGSGJ(B. (3ceG Je JMdjd JCKjQ eYGjjQ EYGOI GdHfGA GdeNJdaI eKd MLe GdeUahaI, MLe GdahcSd, YOO GdJcQGQGJ hGdeLehYGJ, hGdJQTjM HYO EYGOI GdHfGA (B(postfiltering). (3CXgQJ GdfJGFL Cf VHW eYGjjQ EYGOI GdHfGA jSGge HTcd cHjQ aj JMSjf ObI JMOjO MLe GdhQe hJbdjd BKGQ GdMLe GdLRFj hJThgGJ LjHS(B. (3ceG Cf GdGdJRGe HJhUjGJ GdeYGjjQ GdOhdjI jSge aj JYRjR bGHdjI GdebGQfI hGdehKhbjI Hjf CLgRI (BPET (3GdeNJdaI(B. (3JOYe gPg GdfJGFL GSJNOGe GSJQGJjLjGJ EYGOI HfGA eNUUI dJMbjb bjGSGJ cejI ObjbI hehKhbI aj GdJWHjbGJ GdSQjQjI hGdHMKjI(B.s
Thesis (Ph.D)-Cairo University, 2025.
Bibliography: pages 50-53.
Issues also as CD.
Text in English and abstract in Arabic & English.
Keywords: Medical Biophysics; (3GdajRjGA GdMjhjgs; standardized uptake value -- time of flight -- point spread function -- reconstruction optimization -- partial volume effect -- (SUV) (3bjeI GdGeJUGU GdbjGSjI s -- (TOF) (3Ref GdWjQGf s